2021
DOI: 10.3390/nu13082752
|View full text |Cite
|
Sign up to set email alerts
|

Do Breastfeeding History and Diet Quality Predict Inhibitory Control at Preschool Age?

Abstract: Inhibitory control is the ability to control impulsive behavior. It is associated with a range of mental and physical health outcomes, including attention deficit hyperactivity disorder and substance dependence. Breastfeeding and healthy dietary patterns have been associated with better executive functions, of which inhibitory control is part. Additionally, breastfeeding has been associated with healthy dietary patterns. Following our preregistration in the Open Science Framework, we investigated the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“… 61 However, in this study, it is unknown if the increased level of Prevotella _9 is caused by breastfeeding or other relevant dietary factors. In a recent study based on another population, we found that longer exclusive breastfeeding duration was associated with a healthier child diet at age 3 years, 62 note though that, as mentioned before, diet at age 10 was unrelated to child gut microbiota. Further studies aiming to validate this association and explore causality are hence needed to clarify these issues.…”
Section: Discussionsupporting
confidence: 62%
“… 61 However, in this study, it is unknown if the increased level of Prevotella _9 is caused by breastfeeding or other relevant dietary factors. In a recent study based on another population, we found that longer exclusive breastfeeding duration was associated with a healthier child diet at age 3 years, 62 note though that, as mentioned before, diet at age 10 was unrelated to child gut microbiota. Further studies aiming to validate this association and explore causality are hence needed to clarify these issues.…”
Section: Discussionsupporting
confidence: 62%
“…Finally, while during the prenatal and postpartum assessment rounds all mothers and fathers were assessed in the late afternoon and early evening to control for the circadian variation in CORT and T concentrations, the visits during toddlerhood took place in the morning and in the afternoon. This was because the main focus of this visit was to investigate children's executive functioning and we aimed to test children to the best of their abilities (for more information on the procedure and content of the visit, see Willemsen et al, 2021). Though we controlled for assessment time when investigating maternal and paternal toddlerhood CORT and T associations with caregiving quality, future research should aim to restrict assessment times to the second part of the day when cortisol concentrations are slowly decreasing (Adam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, home visits took place, where child inhibitory control was assessed by a trained examiner through six inhibitory control tasks. For more information on the procedure and content of the visit, see Willemsen et al [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Ratings of Everyday Executive Functioning (REEF) is less commonly used and rates child executive functions in different situations (e.g., executive functions around friends, during grocery shopping, or in the community). Because of their different assessment methods, and because previous literature showed different outcomes between the two questionnaires [ 43 ], we included both in our research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation